2022
DOI: 10.3389/fvets.2022.908255
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Integration Analysis at Different Embryonic Ages Reveals Key lncRNAs and mRNAs for Chicken Skeletal Muscle

Abstract: The growth and development of skeletal muscle at embryonic stages are vital and it directly affects the growth performance of chickens. Long non-coding RNA (lncRNA) plays an important role in this process. In the experiment, we collected the leg muscles of fast- and slow-growing Bian chickens both at 14- and 20-day embryo ages (14E and 20E) for RNA-seq. Finally, 292 and 347 differentially expressed (DE) lncRNAs were identified in F14vsF20 and S14vsS20, and 1,295 and 1,560 DE mRNAs were also screened, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Noncoding RNA (ncRNAs), although neglected in the past, have been increasingly studied in recent years to show that noncoding RNAs play important regulatory roles in gene expression networks that affect many biological processes or diseases ( Chen et al, 2021 ; Wu et al, 2022 ; Xiao et al, 2022 ). In this study, we obtained 205 DE lncRNAs and 16 DE miRNAs in uterine tissues from the NE and PE groups.…”
Section: Discussionmentioning
confidence: 99%
“…Noncoding RNA (ncRNAs), although neglected in the past, have been increasingly studied in recent years to show that noncoding RNAs play important regulatory roles in gene expression networks that affect many biological processes or diseases ( Chen et al, 2021 ; Wu et al, 2022 ; Xiao et al, 2022 ). In this study, we obtained 205 DE lncRNAs and 16 DE miRNAs in uterine tissues from the NE and PE groups.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that CDK1 plays an important role in the regulation of skeletal muscle development in chickens and mice and acts as a marker gene for myoblast proliferation ( Cai et al, 2018 ; Xiong et al, 2023 ). Wu et al (2022) studied Bian chicken leg muscle transcriptomic data from different embryonic periods and found that PLK1 and CDK1 may play regulatory roles in muscle development. In addition, PLK1 and CDK1 regulate centrosome segregation in chicken ( Smith et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…As one of the most important members of the ncRNA family, lncRNA plays a vital role in regulating the transcriptional and post-transcriptional expression of genes in muscles [ 7 , 17 ]. In the past, numerous lncRNAs have been discovered in livestock, and these molecules are demonstrated to have a key role in the development of a variety of tissues [ 6 , 8 , 18 , 19 , 20 ]. However, there are few studies on lncRNA transcriptome in muscle cell development, since most studies are conducted at the tissue level.…”
Section: Discussionmentioning
confidence: 99%